Characteristics of Smallholder Coconut Cultivation in North Aceh - Khaidir; Usnawiyah; Muhammad Yusuf Nurdin; Elvira Sari Dewi; Angga Yuda Alfitra; Muhammad Luthfi Pohan; Raihan Zarwa Harahap (LPPM Universitas Malikussaleh, 2022)
Cocosnucifera L. farms in Indonesia are smallholder plantations, and the cultivation methods used have not been properly considered, leading to a low yield.The study aimed to identify the coconut cultivation method and evaluate the systems' suitability according to the recommendation on small-scale farmer plantations in the North Aceh regency. Within the North Aceh regency, we interviewed 135 coconut farmers in three different districts, i.e., Baktiya, Sawang, and Dewantara.The data collected and analysed using R-studio and the non-parametric chi-square test. Around 83% of the respondent in Sawang practice mixed culture in coconut farming, 53% in Baktiya, and 40% in Dewantara. The majority of the coconut variety planted is from the farmer's local garden.Coconuts are usually harvested manually by climbing, with harvesting occurring three to four times each year.Coconuts are picked and shipped immediately to collectors without prior sorting or storage.The annual production of coconuts varies significantly amongst the three districts. Baktiya produces approximately 4.87 tonnes of coconuts annually, while Sawang and Dewantara yield 1.34 tonnes and 0.80 tonnes, respectively.In general, respondents have not carried out the cultivation process in accordance with regional recommendations for planting coconuts.